Eksplorasi Warisan Sejarah Dan Budaya Islam Di Tanah Jambi - Yosephine Sinurat, Junita; Muntamah, Siti; Meihan, Andre Mustofa (CHRONOLOGIA, 2024)
This article aims to discuss the richness of Islamic cultural heritage in the magnificent Land of Jambi. Through exploration of the history, heritage, values, and influence of Islam in Jambi, readers are invited to explore the rich and deep cultural footprint. From the history of the entry of Islam, the beauty of Islamic architecture and art, to the values upheld in local society, this article reveals the diversity and splendor of Islam in the area. The method used in this study is a historical method consisting of 4 parts, namely Heuristics, Source Criticism, Interpretation, and Historiography. The type of source used in this study is collecting secondary sources, which are obtained through the process of document study which in this case can be in the form of data archives that discuss the richness of Islamic cultural heritage in the magnificent Land of Jambi, as well as scientific journals that discuss Islamic cultural heritage in Jambi Land. The result of this research is that Islam entering Jambi has a very much influence on the lives of Jambi people. This can be seen from the many changes in the order of social life, Islamic cultural relics, and even traditions that were present after Islam entered Jambi.